Brazilian initial experience with lung transplantation due to irreversible lung fibrosis post-COVID-19 in a national reference center: a cohort study - Reis, Flavio Pola dos (2022)
BACKGROUND: Lung transplantation (LTx) has been discussed as an option for treating irreversible lung fibrosis post-coronavirus disease 2019 (COVID-19), in selected cases. OBJECTIVES: To report on the initial experience and management of end-stage lung disease due to COVID-19 at a national center reference in Brazil. DESIGN AND SETTING: Cohort study conducted at a national reference center for lung transplantation. METHODS: Medical charts were reviewed regarding patients’ demographics and pre-COVID-19 characteristics, post-LTx due to COVID-19. RESULTS: Between March 2020 and September 2021, there were 33 cases of LTx. During this period, we evaluated 11 cases of severe COVID-19-related acute respiratory distress syndrome (ARDS) that were potentially candidates for LTx. Among these, LTx was only indicated for three patients (9.1%). All of these patients were on venovenous extracorporeal membrane oxygenation (ECMO), and the procedure that they underwent was central venoarterial ECMO. All three patients were still alive after the first 30 postoperative days. However, patient #1 and patient #2 subsequently died due to fungal sepsis on the 47th and 52nd postoperative days, respectively. Patient #3 was discharged on the 30th postoperative day. CONCLUSIONS: LTx is feasible among these complex patients. Survival over the first 30 days was 100%, and this favors surgical feasibility. Nonetheless, these were critically ill patients.